THE INFLUENCE OF IMPROVING THE ANWAR IDRIS ROAD SECTION ON REGIONAL DEVELOPMENT IN TANJUNGBALAI CITY - Ningsih Farida Manalu; Cut Nuraini; Abdi Sugiarto (Bulletin of Engineering Science, Technology and Industry, 2025)
The upgrading of Anwar Idris Road in Tanjungbalai City is an important project that aims to improve the quality of infrastructure and facilitate the movement of goods and services. This study examines the social, economic, and environmental impacts arising from the construction of the road. The results show that the road upgrade provides significant benefits in terms of accessibility and economic opportunities for the community, but also poses challenges such as socio-economic inequality, air pollution, congestion, and land use change. This study suggests the need for more inclusive planning, efficient traffic management, and policies that focus on environmental sustainability to ensure sustainable benefits for the wider community.